Relationship of Salmonella isolation with different serum and inflammatory intestinal parameters in natural fowl typhoid outbreaks from laying hens - Soria, Mario (2023)
Our study was undertaken to determine the best samples and selective-diﬀerential plating media to be used for Salmonella spp. isolation. We also compared hematological and serum biochemical values, Salmonella biovar Gallinarum (SG) detection (isolation and serological test), and inflammatory intestinal response (fecal leukocyte) in laying hens with naturally occurring fowl typhoid outbreaks. Furthermore, we looked for a biomarker of SG infection. Spleen, liver, ovarian follicle content, and bone marrow were found to be the best samples for SG isolation and the agreement between MacConkey-Salmonella Shigella agar was slight to excellent. The laying hens with SG isolation and rapid serum plate agglutination positive results showed a higher percentage of heterophils, heterophil/lymphocyte ratio and total white blood cells, and a lower percentage of lymphocytes than those with negative results. Furthermore, the positive fecal leukocyte samples had a higher percentage of heterophils, gamma-glutamyl transferase, total protein and globulin values than negative samples. Five biomarkers’ cut-offs are proposed to distinguish between laying hens positive and negative to SG isolation.